Paraspinal Abscess Secondary to Spondylodiscitis: A Rare Presentation with Progressive Neurological Deficits and Systemic Infection - Putra, I Gusti Ngurah Paramartha Wijaya; Wijaya, I Gusti Ngurah Paramartha; Febyan, Febyan; Yulian, Kenny (Indonesian Journal of Medicine, 2025)
Background: Spondylodiscitis is a rare but serious spinal infection that may result in neuro-logical and systemic complications, especially when associated with paraspinal abscess formation. This case highlights its clinical severity and the importance of early intervention. This study aims to highlight the clinical importance and potential severity of spondylodiscitis, particularly when complicated by paraspinal abscess formation. Case Presentation: A patient presented with progressive lower back pain, bilateral lower limb weakness, and systemic symptoms including fever and night sweats. Laboratory tests revealed hypoalbuminemia, leukocytosis, and anemia. MRI imaging identified a paraspinal abscess at the L3–L5 levels, resulting in lumbar canal stenosis and worsening neurological deficits. Emergency surgical intervention was undertaken, consisting of abscess drainage, laminectomy for neural decompression, and posterior spinal stabilization. Intraoperative findings included a substantial purulent collection, necessitating extensive debridement. Postoperatively, the patient demonstra¬ted clinical improvement with ongoing antibiotic therapy, nutritional support, and rehabilitation. Discussion: Spondylodiscitis with paraspinal abscess is a diagnostic challenge due to its insidious onset and non-specific presentation. Delayed recognition increases the risk of severe neurological impairment and systemic sepsis. MRI is the gold standard for early detection, while micro¬biological confirmation is crucial for targeted treatment. A multidisciplinary approach is essential. Surgical intervention is indicated for progressive neurological deficits, extensive abscess formation, or spinal instability, with timely antibiotic therapy playing a critical role in infection control. Conclusion: This case illustrates the importance of early diagnosis and timely surgical manage-ment in spondylodiscitis with paraspinal abscess. Multimodal treatment improves outcomes and helps prevent long-term disability.